Diversity along a speciation continuum : ecology and morphology of northern European whitefish (Coregonus lavaretus) - Siwertsson, Anna (University of Tromsø, 2012)
Papers 1 and 4 of this thesis are not available in Munin: 1. Anna Siwertsson, Rune Knudsen and Per-Arne Amundsen: 'Temporal stability in gill raker numbers of subarctic European whitefish populations', Advances in Limnology (2012), vol. 63:229-240. Available at http://www.schweizerbart.de/papers/adv_limnology/detail/63/77932/Temporal_stability_ingill_raker_numbers_of_subarct 4. Anna Siwertsson, Rune Knudsen, Colin Adams and Per-Arne Amundsen: 'Replicated morphological divergence supports incipient ecological morph formation in European whitefish (Coregonus lavaretus)', (manuscript) How new species are formed is still a major question in evolutionary biology. In ecological speciation, natural selection drives the evolution of slight distinctions between individuals into extensive differences between species. In this thesis, early stages of an ecologically driven speciation process are addressed using ecological and morphological data from a large number of European whitefish (Coregonus lavaretus) populations in northern Fennoscandia. Northern Fennoscandia is an area scattered with lakes created during the glacial retreat (~10-12 kyr BP). Many of these lakes are inhabited by one or up to three different morphs of whitefish. As many other temperate freshwater fishes, whitefish typically diverge into pelagic and littoral resource specialists, the densely rakered (DR) and the large sparsely rakered (LSR) morph, respectively. Parallel within-lake divergence is the most probable origin of these sympatric morphs. In addition, a third whitefish morph (the small sparsely rakered; SSR), specializing on profundal resources, was recently described in a few lakes in the area. The aims of this thesis were to explore and document the phenotypic diversity of whitefish in northern Fennoscandia, and to investigate some of the factors limiting the level of diversity reached within each lake. Further, the ability of LSR whitefish morphs to utilize profundal resources was explored, as this is a probable origin of profundal ...